The Fokker-Planck equation : methods of solution and applications / H. Risken. - Risken, H. (Hannes), 1934- (Springer series in synergetics, 2012)
One of the central problems synergetics is concerned with consists in the study of macroscopic qualitative changes of systems belonging to various disciplines such as physics, chemistry, or electrical engineering. When such transitions from one state to another take place, fluctuations, i.e., random processes, may play an important role. Over the past decades it has turned out that the Fokker-Planck equation pro- vides a powerful tool with which the effects of fluctuations close to transition points can be adequately treated and that the approaches based on the Fokker-Planck equation are superior to other approaches, e.g., based on Langevin equa- tions. Quite generally, the Fokker-Planck equation plays an important role in problems which involve noise, e.g., in electrical circuits.